2009
DOI: 10.1097/bpo.0b013e3181c1e2fa
|View full text |Cite
|
Sign up to set email alerts
|

Motocross Morbidity: Economic Cost and Injury Distribution in Children

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
51
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 10 publications
2
51
1
1
Order By: Relevance
“…A previous retrospective review of motocross injuries treated at our institution from 2000 to 2007 identified 299 motocross injuries in 249 unique pediatric patients. 18 Of these 299 injury episodes, 141 (47%) required hospital admission, consistent with prior studies that show 20 to 30 admissions annually from motorbike injuries. Furthermore, 19 patients (6%) required admission to an intensive care unit, and 91 (30%) required surgical interventions (89% of which were orthopedic in nature).…”
supporting
confidence: 81%
See 3 more Smart Citations
“…A previous retrospective review of motocross injuries treated at our institution from 2000 to 2007 identified 299 motocross injuries in 249 unique pediatric patients. 18 Of these 299 injury episodes, 141 (47%) required hospital admission, consistent with prior studies that show 20 to 30 admissions annually from motorbike injuries. Furthermore, 19 patients (6%) required admission to an intensive care unit, and 91 (30%) required surgical interventions (89% of which were orthopedic in nature).…”
supporting
confidence: 81%
“…Larson et al 18 reported loss of consciousness in 18% of all documented motocross injuries. These data were obtained from patient registries, meaning that participants with less recognizable or reportable symptoms of CBIs on the racetrack may not have presented to the hospital or emergency room.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature review reveals a significant body of information regarding the epidemiology of either specific fractures (craniofacial [21], maxillofacial [22], wrist/distal radius [23,24], hand [25,26], knee [27], tibial tuberosity [28] or metatarsal bones [29]) or certain activity-related injuries (motocross [30], all-terrain vehicles [31], bicycle [32], falling down the stairs [33] or holiday-related [34]). However, the objective of the study was to address the epidemiology of MSP in the ED and not the epidemiology of pediatric fractures or injuries.…”
Section: Discussionmentioning
confidence: 99%